Husserlio fenomenologijos horizontai - Jonkus, Dalius (Problemos, 2016)
Saulius Geniusas. The Origins of the Horizon in Husserl’s Phenomenology. Dordrecht: Springer, 2012. 243 p. (Contribution to Phenomenology 67). ISBN 978-94-007-4643-5